2013
DOI: 10.1021/jp402297n
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Doping of Hexagonal Boron Nitride by Using CO Molecules

Abstract: The fabrication of carbon (C) doped hexagonal boron nitride (h-BN) has attracted more and more attention due to its widespread applications. A novel method of constructing custom-designed C doped h-BN via CO molecules interaction with the vacancy defect h-BN is demonstrated in this paper using density functional theory (DFT) calculations. The reaction process consists of the CO-vacancy recombination and extra O removal by CO; thus, C doped h-BN is formed without introducing additional defects. According to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 43 publications
2
38
1
3
Order By: Relevance
“…These primarily electrostatic interactions have also been found in the Na-montmorillonite system [38]. To investigate the effect of the polarity of kerogen moieties on the extraction of the kerogen moieties with supercritical CO 2 , the dipole moments of the four molecules were calculated by the first-principle simulation; the details of the simulation have been reported in our previous work [50][51][52]. The dipole moments of [53,54].…”
Section: The Effect Of the Polarity Of Kerogen Moieties On Extractionmentioning
confidence: 86%
“…These primarily electrostatic interactions have also been found in the Na-montmorillonite system [38]. To investigate the effect of the polarity of kerogen moieties on the extraction of the kerogen moieties with supercritical CO 2 , the dipole moments of the four molecules were calculated by the first-principle simulation; the details of the simulation have been reported in our previous work [50][51][52]. The dipole moments of [53,54].…”
Section: The Effect Of the Polarity Of Kerogen Moieties On Extractionmentioning
confidence: 86%
“…The carbon atoms substituting boron atoms give rise to an unpaired electron and induce a local magnetic moment ( Figure a) . Constructing custom‐designed C doped h‐BN via interaction of CO molecules with vacancy defects in h‐BN has been demonstrated theoretically . Besides carbon, transition‐metal atoms are also good dopants for h‐BN to yield interesting electronic and magnetic properties, which depend on the dopant species (Figure b) and are tunable by electric field .…”
Section: Synthesis Properties and Applications Of Two Dimensional H‐bnmentioning
confidence: 99%
“…33 Lu et al shown that the Se vacancy of the WSe 2 monolayer can be effectively repaired by O atoms and the conductivity and photoconductivity of the material can be enhanced by two order-of-magnitude compared with the untreated sample. Based on the first-principles calculation, the repairing atomic vacancy for the low-dimensional materials has been theoretically explored previously for graphene 34,35 and boron nitride [36][37][38] . 19 The above studies suggest that the chalcogen vacancies in TMDs may be able to be repaired by using external molecules.…”
Section: Introductionmentioning
confidence: 99%
“…19 The above studies suggest that the chalcogen vacancies in TMDs may be able to be repaired by using external molecules. 38 In this study, the repairing process of the MoS 2 monolayer containing single S vacancies has been theoretically investigated by the adsorption of CO, NO and NO 2 molecules. For example, Wang et al studied the healing of the C vacancy and the N doping in graphene by CO and NO molecules, respectively.…”
Section: Introductionmentioning
confidence: 99%